Design of customized business process management with implementation in the apparel industry as a solution to achieve operational excellence - Prabowo Sutjiatmo, Bayu; Nurkomariyah, Siti; Enggar Tyasti, Avia; Ciputra Daeng Bani, Fajar (Edelweiss Applied Science and Technology, 2024)
Textile industry companies are required to compete optimally with competitors to generate higher revenues for the sustainability of the company. In addition, companies must be responsive to market demands because of the dynamic nature of the market. One of the systems used to meet these needs is the Enterprise Resource Planning (ERP) information system. PT Rofina Indah Jaya (Poshboy) has obstacles in implementing ERP in the apparel industry because it is still too generic and has not been optimal in using the existing ERP system. This study aims to improve the performance and efficiency of the industry that produces real-time business reports, so that effective and efficient coordination is created. The methodology used in this study is to take a qualitative and quantitative approach to investigate the design of business process management that is adjusted to the implementation in the apparel industry as a solution to achieve operational excellence. Designing ERP based on customized business processes with implementation in the apparel industry is waterfall is a sequential development process and RACI Matrix that can be adopted to ensure the improvement process runs consistently. Optimization of the ERP business process uses Business Process Management (BPM) by identifying processes that require improvement through comprehensive process mapping to understand the overall workflow. So that ERP can manage customer relationship management (CRM), stock availability updates, warehouse stock positions, goods in transit, order placement, delivery orders, as well as recording and finance used for management decision-making analysis